Re‐emergence of rabies in Mazowieckie Voivodeship, Poland, 2021. (12th October 2022) - Smreczak, Marcin; Orłowska, Anna; Trębas, Paweł; Stolarek, Agnieszka; Freuling, Conrad; Müller, Thomas
Abstract: Due to the oral vaccination of foxes against rabies most of the territory of Poland was freed from rabies of non‐flying mammals. In January 2021, rabies was diagnosed in fox in the central part of Mazowieckie Voivodeship where rabies has not been detected since last 17 years. Subsequently, in the following months the rabies virus infection spread southward reaching the voivodeship of Świętokrzyskie in November 2021. Emergency actions were implemented aiming at rapid rabies elimination.